Reflections on the global food crisis: How did it happen? How has it hurt? And how can we prevent the next one? - Headey, Derek D.; Fan, Shenggen (International Food Policy Research Institute, 2010)
Cheap food has been taken for granted for almost 30 years. From their peak in the 1970s crisis, real food prices steadily declined in the 1980s and 1990s and eventually reached an all-time low in the early 2000s. Rich and poor governments alike therefore saw little need to invest in agricultural production, and reliance on food imports appeared to be a relatively safe and efficient means of achieving national food security. However, as the international prices of major food cereals surged upward from 2006 to 2008 these perceptions quickly collapsed. Furthermore, although food prices are now lower than their 2008 peak, real prices have remained significantly higher in 2009 and 2010 than they were prior to the crisis, and various simulation models predict that real food prices will remain high until at least the end of the next decade.